Experimental and numerical investigations of electromagnetic crimping process for joining of helicopter structures - Güzel, A.; Rohr, T.; Lueg-Althoff, J.; Beu, M.A.; Hahn, M.; Tekkaya, A.E. (My University, 2019)
The present study investigates the electromagnetic crimping process as an alternative to thermally welded joints with different form-fit elements like grooves, pockets, and knurlings. The electromagnetic joining technology is based on pulsed magnetic fields to shape components made of electrically conductive materials and it is able to manufacture form-fit or welded joints. First, the analytical methods are presented to design a lightweight helicopter’s cyclic stick by the electromagnetic joining process based on maximum applied pilot control forces. Furthermore, approaches to calculate the maximum axial and torsional load transfer between the joining partners are given. The results are used in a two dimensional finite-element simulation to determine the process parameters and to optimize the groove design with respect to shear stresses. A good agreement between the numerical results and the experimental investigations is shown. The pull-out force is set as the failure criterion of the connection and the specific joint strength of different groove shapes is compared with the analytical model. Due to the slight increase of the total weight at the presented weight analysis, proposals for design optimization with focus on the joining zone are made. Despite this fact, the cost analysis shows a reduction of production costs. The achieved main goal of the presented study is the proof of feasibility of substituting thermally welded connections with electromagnetically crimped joints made of lightweight components and the proof of the remarkable potential of reducing production costs and time of aeronautic components.